Risk of Carbon Monoxide (CO) Exposure to Street Vendors in Bandar Lampung City - Azzahra Tazkia Cartama; Prayudhy Yushananta (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2025)
High motor vehicle activity can be harmful to health. However, no research has specifically analyzed the risk of carbon monoxide (CO) exposure among street vendors in Bandar Lampung. The study aims to analyze the health risks associated with CO exposure among street vendors in Bandar Lampung City. The study used a case study design, employing an Environmental Health Risk Analysis (EHRA) approach, with 34 street vendors in Teuku Umar Street, Bandar Lampung City. The study was conducted from April to May 2025. Measurements of CO concentration and vehicle counts were conducted at three points using the Non-Dispersive Infrared (NDIR) method for 7 days, with 3 replications (morning, afternoon, and evening). So that 63 data points were obtained (N = 63). Exposure analysis was conducted on 34 traders purposively selected at each sample point. Furthermore, the data was analyzed to obtain a risk value (RQ). The study results found that the average CO concentration was 6721 mg/m3 (1340 -11112 mg/m3 ). The average number of vehicles was 2,814 units (93 - 6,324 units). Statistical analysis showed a very strong relationship between the number of vehicles and ambient CO levels (r = 0.807; P = 0.001). The risk analysis found that all respondents had RQ values> 1, indicating that CO exposure is associated with health risks. The study found that all respondents were at risk of health problems from CO exposure. In addition, it has been shown that ambient CO levels are closely correlated with the number of vehicles.